China's Trade Unions - How Autonomous Are They? : a Survey of 1811 Enterprise Union Chairpersons. - Hishida, Masaharu (China policy series., 2009)
Examines the status of trade unions in contemporary China, exploring the degree to which trade unions have been reformed as China is integrated into the global economy. With empirical research data, this book discusses the key question of how autonomous China's trade unions are.